2019
DOI: 10.3389/fpsyg.2019.02258
|View full text |Cite
|
Sign up to set email alerts
|

The Context-Variable Self and Autonomy: Exploring Surveillance Experience, (Mis)recognition, and Action at Airport Security Checkpoints

Abstract: This paper critiques and extends the notion of autonomy by examining how common autonomy definitions construct selfhood, with the support of an analysis of airport surveillance experiences. In psychology, autonomy is (1) often oriented around volition and action rather than the-self-that-acts and (2) the-self-that-acts is construed in singular terms. This neglects the multiple, context-variable self: while others may confirm our self-definitions (recognition), identity claims may also be rejected (misrecogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Our research adds detail to previous studies on misrecognition and racism. For instance, research on misrecognition in airport security showed that misrecognition was treated as racism to the extent that it functioned in racialized terms (e.g., singling out people by nationality or ethnic appearance) and communicated a lack of belonging (Blackwood et al., 2013b; McNamara & Reicher, 2019). We have illustrated how accounts of such incidents are worked up publicly, managed sensitively, and depend on their reception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research adds detail to previous studies on misrecognition and racism. For instance, research on misrecognition in airport security showed that misrecognition was treated as racism to the extent that it functioned in racialized terms (e.g., singling out people by nationality or ethnic appearance) and communicated a lack of belonging (Blackwood et al., 2013b; McNamara & Reicher, 2019). We have illustrated how accounts of such incidents are worked up publicly, managed sensitively, and depend on their reception.…”
Section: Discussionmentioning
confidence: 99%
“…They noted that participants reported having to manage both the incorrect attribution of religious affiliation and racist assumptions associated with Islam. In one account in McNamara and Reicher's (2019) study, misrecognition was described as 'kind of racist' by one of the participants but most instances cited did not explicitly characterize misrecognition as racism. Rawls and Duck (2017), by contrast, made direct connections with racism in their interviewed-based study of accounts of 'nonrecognition' from Black men in professional contexts in the United States.…”
Section: Misrecognition and Racismmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of power leads to a lack of autonomy on two levels: to define and to act upon one's own identity (McNamara & Reicher, 2019). Misrecognition is thus a materialisation of negative power in which powerful others impose identities on the relative disempowered.…”
Section: Misrecognition and Powermentioning
confidence: 99%
“…Thus, practical management tools have become necessary for both airports and airlines in the process of optimizing the security processes while keeping a high customer service level and profitability¹. (McNamara & Reicher, 2019).…”
mentioning
confidence: 99%